Demonstration for the release of the 'Pentonville Five' - painting 1973 (London, 1973)
1973 1970-74 "Demonstration for the release of the 'Pentonville Five' - painting 1973" [BW0022], 1973, Trades Union Congress During the 1972 dock strike, five dockers were arrested on the picket line, committed for contempt and put in Pentonville Prison. This painting, showing the massive demonstration outside the prison four days later on 25 July, was completed by Dan Jones in 1973. The painting is owned by the TUC and now hangs outside the General Council Chamber inside Congress House